Self-Destruction of Idols in Arab Muslim Historiography: An Influence of Eastern Christian Hagiography? - Frantsouzoff, Serge A. (Scrinium, 2023)
The article deals with a potential source and the subsequent borrowing of the motif of the self-destruction of the pagan idols. This motif is common in Eastern Christian apocrypha and hagiographic tales and also in the Arab Islamic tradition. In Muslim historiography, among stories about the destiny of ancient Arabian images, such a motif is found only twice. Both legends are connected with pre-Islanic Ḥaḍramawt, the autonomous region in Yemen. One legend deals with the idol called al-Djalsad, an object of veneration mostly by a tribe of al-Sakūn. It was represented in the shape of a white anthropomorphic rock with a black head. The other tale narrates about the domestic statue made of cornelian that belonged to the local notable Wā’il b. Ḥudjr. The subject of the spontaneous fall of idols appears to reflect a rivalry, especially in the spiritual sphere, between the tribal confederation al-Sakūn and the descendants of the indigenous sedentary population of Ḥaḍramawt. Their struggle for power in the early Islamic empire manifested in the most apparent way in Egypt, where they could borrow the motif of idols’ self-destruction from the Copts. Thus, in Chapter LXXIX of the Chronicle by John of Nikiu compiled in the late 7th–early 8th century AD obviously in Greek a tale about the childhood of St Theophilus, the Coptic Patriarch in AD 385–412, is preserved. According to it, in his presence, the statues of Artemis and Apollo became overthrown in a shrine situated in the district of Memphis.